Body composition and strength parameters in elite judo athletes 5 years after anterior cruciate ligament reconstruction - Prill, R.; Michel, S.; Schulz, R.; Coriolano Appell, H.-J, (International Journal of Sports Medicine, 2019)
The purpose of this study was to investigate if there are still deficits in muscle mass or strength capabilities in elite judo athletes with a history of anterior cruciate ligament reconstruction (ACLR) after their return to the sport. Therefore, bioimpedance analysis, 3D-laser thigh circumference measurement and isokinetic dynamometry in a closed kinetic chain were used. The side-to-side differences were investigated in a group of judo athletes 5 years after ACLR (n=17) and compared with a group of healthy judo athletes (n=27). Neither thigh circumferences, nor muscle masses of the lower extremities differed in formerly injured judo athletes compared to healthy judo athletes. In contrast, isokinetic strength testing showed a significantly larger side-to-side difference of peak muscle force in formerly injured judo athletes (p=0.021). They provided significantly lower peak forces with the formerly injured leg than with the non-injured leg (p<0.001). The authors conclude that strength capabilities, but not body composition, remains altered in recovered judo athletes in mean 5 years after ACLR and definitely after their return to sports. This indicates that the focus of rehabilitation protocols and return to sports assessments should focus more on maximum strength capabilities.